Question
Which pair shows equivalent expressions? \( 2 x+10=-2(x-5) \) \( -2(x+5)=2 x-10 \) \( -2 x-10=-2(x+5) \) \( -2(x-5)=-2 x-10 \)
Ask by Montgomery Conner. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
The first and second equations are equivalent, both giving \( x = 0 \).
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Mind Expander
The pair that shows equivalent expressions is: \( 2 x + 10 = -2(x - 5) \) – When you simplify the right side, you get \( -2x + 10 \), which can be rearranged to match the left side, confirming they're equivalent. \( -2(x - 5) = -2x - 10 \) – Expanding this expression gives you the same \( -2x + 10 \) as previously derived, establishing equivalency. So, \( 2x + 10 \) and \( -2(x - 5) \) are indeed equivalent!